Expression of hedgehog signaling molecules as a prognostic indicator of oral squamous cell carcinoma - Wang, Yi-Fen; Chang, Chun-Ju; Lin, Chin-Ping; Chang, Shyue-Yih; Chu, Pen-Yuan; Tai, Shyh-Kuan; Li, Wing-Yin; Chao, K.S. Clifford; Chen, Yu-Jen (Head & neck, 2012)
Background Recent studies have indicated hedgehog pathway plays a role in carcinogenesis of certain cancers. We investigated the clinical significance of its signaling components, including Sonic hedgehog (Shh), Patched (Ptch), and Gli‐1, in oral squamous cell carcinoma (OSCC). Methods By immunohistochemistry, we determined Shh, Ptch, and Gli‐1 expression in surgical specimens from 40 patients with OSCC. The relationship between expression of these molecules and clinicopathologic variables were assessed by chi‐square analysis. Statistical difference of survival was compared using log‐rank test. Results Ptch overexpression was associated with lymphatic metastasis (p = .028). Nuclear Gli‐1 overexpression correlated with primary tumor size (p = .001), lymphatic metastasis (p = .011), and tumor recurrence (p = .008). Overexpression of Ptch (p = .020) or Gli‐1 (p = .002) in OSCC indicated poor prognosis in the univariate survival analysis. Conclusion Our results suggest sonic hedgehog (Shh) pathway plays an important role in OSCC progression and should be considered a potential therapeutic target. © 2012 Wiley Periodicals, Inc. Head Neck, 2012